2017
DOI: 10.2174/1871530316666161026142930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Methadone on ECG Characteristics and Endocrine Hormonal Changes and Their Inter-relationship

Abstract: Electrocardiographic changes are an important complication of methadone that seems to be related to low testosterone level in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Methadone therapy for opioid abuse does not change FSH levels in pre-and post-menopausal females (30). Psychoneuroendocrinology consuming prescribed sustained-action opioids in women receiving opiate drug treatment for pain management, including methadone, lead to reductions in FSH levels, whereas FSH levels in pre-menopausal females are not changed from premenopausal controls.…”
Section: Effect Of Methadone On Luteinizing Hormone and Follicle Stim...mentioning
confidence: 95%
See 2 more Smart Citations
“…Methadone therapy for opioid abuse does not change FSH levels in pre-and post-menopausal females (30). Psychoneuroendocrinology consuming prescribed sustained-action opioids in women receiving opiate drug treatment for pain management, including methadone, lead to reductions in FSH levels, whereas FSH levels in pre-menopausal females are not changed from premenopausal controls.…”
Section: Effect Of Methadone On Luteinizing Hormone and Follicle Stim...mentioning
confidence: 95%
“…Serum samples from females receiving methadone for pain management revealed no changes in estradiol levels compared to control group samples (32). Bonakdaran et al reported that methadone has no significant effect on estradiol levels in women receiving methadone therapy for opioid abuse (30). However, another study indicated that estradiol levels reduce in menopausal women receiving methadone for chronic pain in comparison to the pre-menopausal control group (31).…”
Section: Effect Of Methadone On Estrogenmentioning
confidence: 96%
See 1 more Smart Citation